Hybrid Catenary-Battery Trains for Non-Electrified Sections and Emergency Use - Muhammad Nizam; Hari Maghfiroh; Mufti Reza Aulia Putra; Anif Jamaluddin; Inayati Inayati (Universitas Muhammadiyah Magelang, 2025)
The hybrid catenary”“battery system offers a promising solution for railways operating in non-electrified sections and during emergencies, ensuring uninterrupted operation, enhanced safety, environmental sustainability, and cost efficiency. This study addresses the challenge of determining an appropriate battery size and introduces a novel rule-based Energy Management Strategy (EMS) with coasting mode to minimize energy consumption while meeting operational requirements. The novelty of this work lies in (i) a straightforward sizing method based on worst-case emergency scenarios and (ii) the integration of coasting-mode operation into a rule-based EMS for hybrid catenary”“battery trains. Simulation results show that the proposed approach achieves up to 12.56% energy savings on 3% gradient tracks while fully supplying auxiliary loads, compared with baseline operation that provides only partial coverage. These results demonstrate a practical and scalable framework for designing efficient, reliable, and resilient railway transport systems.